Strengthening Puspa Lebo Sidoarjo Development Through Pentahelix Collaboration: A Qualitative Analysis - Tofan Tri Nugroho; Tsabita Karima; Anastasya Putri Hidayat; Bagus Adi Prasetyo (Universitas Muhammadiyah Sidoarjo, 2023)
This study analyzes the development of Puspa Lebo Sidoarjo by employing the pentahelix approach, fostering cooperation among government, industry, academia, society, and the media. Using a qualitative approach with in-depth interviews, direct observation, and documentation, the study demonstrates that the pentahelix approach effectively enhances the area's development. The local government provides policy and regulatory support, enabling East Java agribusiness growth, while industry contributes to product development and marketing networks. Academics play a role in product research, development, and human resource improvement. Communities offer support and active involvement in product development and marketing, while the media provides positive coverage and promotions. The implications of this research underscore the significance of collaborative efforts among multiple sectors in regional development, showcasing the potential of the pentahelix model in fostering sustainable growth. Highlight: Pentahelix Collaboration: The study explores the effectiveness of the pentahelix approach, emphasizing the cooperation between government, industry, academia, society, and the media in advancing the development of Puspa Lebo Sidoarjo. Multisectoral Contributions: The research highlights the significant contributions of different sectors in the development process, including the local government's policy support, industry's involvement in product development and marketing, academics' role in research and human resource improvement, community support, and the media's positive coverage and promotions. Sustainability and Growth: The implications suggest that collaborative efforts among multiple sectors are vital for achieving sustainable regional development, showcasing the potential of the pentahelix model in fostering continued growth in the area. Keyword: Puspa Lebo Sidoarjo, Pentahelix Approach, Regional Development, Collaboration, Qualitative Analysis